Behaviour of colloidally-dispersed solid particles in very thin film lubricated contacts - Chiñas-Castillo,F; Spikes,HA (Tribology Series, 2000)
The behaviour of colloidal solid particles dispersed in lubricants is of interest for a number of reasons. Firstly, many of the additives used in lubricants are actually in the colloidal rather than the true, solution state. Secondly, soot in engine oils and lubricant degradation products are generally colloidal. Thirdly, there is an increasing interest in the development of lubricants containing dispersed nanoparticles to limit friction and wear. For all the above it is important to understand when and how colloidal solid particles pass through lubricated contacts and also their behaviour in such contacts. In the current study, the behaviour of dispersed particles covering a range of sizes between 20 and 200 nm diameter has been studied in lubricating contacts. Optical interferometry has been employed to explore the behaviour of such particles in very thin film contacts. Friction has also been measured. Of particular interest was the effect of slide-roll ratio on particle entrainment and the influence of the ratio of the particle diameter to the elastohydrodynamic lubricant film thickness. © 2000 Elsevier Science B.V. All rights reserved.